Breaking Boundaries: The Younger Generation and Careers in Christian Religious Education in Facing Social and Cultural Change - Sutrisno, Rheinhard David (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the perceptions of young people toward a career as Christian Religious Education (CRE) teachers amidst dynamic social and cultural changes. The declining interest in this profession is not solely driven by economic and social status concerns but is also influenced by digitalization, secularization, and a lack of vocational formation from families and churches. Using a descriptive qualitative approach, data were collected through literature review and in-depth interviews with church youth and theology students. The findings reveal that young people still hold potential interest in this vocation when supported by strong theological narratives, integrated mentoring strategies, and 21st-century skills. This research recommends the revitalization of holistic and contextual Christian education systems to address contemporary challenges and rekindle youth interest in pursuing a career as CRE teachers.